Mayflies of the Caucasus Mountains. III. A new representative of the subgenus Rhodobaetis Jacob, 2003 (Baetidae: Baetis) from the South-Western Caucasus - Godunko, Roman J.; Palatov, Dmitry M.; Martynov, Alexander V. (Zootaxa, 2015)
A new species of the subgenus Rhodobaetis Jacob, 2003, namely Baetis (Rhodobaetis) vadimi sp. nov., is described based on immature larvae from several localities in Georgia and Turkey. It is the ninth species of the subgenus for Transcaucasia, following six species formally recorded from Turkey and two endemic species described from the Central Caucasus.         Larval characters are investigated and illustrated by means of scanning electron microscopy, and discussed in details. The differential diagnosis of this species is provided with regard to other representatives of the subgenus considering the feature set common for Rhodobaetis. The new species can be distinguished from its relatives (species which lack stout setae on the gills’ margins), mainly by some characters of mouthparts (particularly labium), the shape and arrangement of stout setae and scales on the body surface, as well as the lack of subapical tiny setae on tarsal claw, and presence of numerous marginal spines and semilunar scale bases on the paraproct plate.